Gambaran Myelosupresi pada pasien Kanker Ovarium yang Menerima Kemoterapi Carboplatin-Paclitaxel di RSUPN Cipto Mangunkusumo Tahun 2018 - Winarto, Hariyono; Wijaya, Andrew (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Background: Ovarian cancer has the highest mortality rate among other gynecologic cancers with poor prognosis due to unspecific symptoms. Ovarian cancer is mainly treated by surgical and chemotherapy combination. Despite its curative effect chemotherapy’s, myelosuppressive is a notable side effect and may impact the next cycle of chemotherapy. This study is aimed to record laboratory changes in chemotherapy recipient in Cipto Mangunkusumo Hospital.Methods: Hemoglobin, Absolute Neutrophil Count (ANC), and thrombocyte data are obtained from medical records whose received 6 cycles of Carboplatin-Paclitaxel from January-December 2018. Patients who received other chemotherapy and bone marrow metastasis were excluded.Results: Sixteen patients who completed 6 cycles were recorded. Baseline hemoglobin was 11.30±0.887 mg/dL and mean reduction was 0.29 g/dL per cycle. Mean ANC was 5,394.43±2096 cells/mm3, mean reduction was 543 cells/mm3 per cycle, and 5,35% developed neutropenia. Mean thrombocyte level was 34.225 cells/mm3 and 23% developed thrombocytopenia.Conclusions: Carboplatin-Paclitaxel’s effect on myelosuppression is prominent within the first cycle. Extra precaution must be done to prevent unwanted events.